Hubungan Karakteristik Individu dengan Keluhan Gangguan Faal Paru pada Pekerja Pengrajin Marmer di Jawa Timur - Ridhani, Akhmad; Ridhayanti, Rizky; Wicaksono, Utomo; Saputri, Juliani; Prayogo, Dadan (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
The home-based marble processing industry is an informal sector with a high risk of pulmonary function disorders due to uncontrolled dust exposure. This study aimed to analyze the relationship between individual characteristics (age, nutritional status, smoking habits, years of service, working hours, and mask use) and pulmonary complaints among marble craftsmen in Tulungagung. A quantitative approach with a cross-sectional design was employed, involving 32 respondents selected using total sampling. Data were collected using the ATS-DLD-78A questionnaire and analyzed with Pearson’s correlation test. Results showed no statistically significant relationship between individual characteristics and pulmonary complaints (p > 0.05), although a negative correlation tendency was found for nutritional status and mask use. These findings highlight the greater influence of occupational environmental factors over individual factors in informal settings. Community-based interventions are recommended to improve workplace conditions and increase education on the use of personal protective equipment to prevent pulmonary function disorders among workers in the home industry.